A combined measure of tuberculous lesions for assessing the efficacy of vaccination against tuberculosis (Mycobacterium bovis) in European badgers (Meles meles) supports the 3Rs principle of reduction. Issue 11 (12th March 2021) - Birch, Colin P.D.; Chambers, Mark A.; Lesellier, Sandrine
Highlights: A new measure (DBS) of tuberculosis improved precision, consistency and uniformity. Using DBS showed that sex, weight and M. avium response influenced TB in badgers. A covariate model reduced error equivalent to using 30% more animals in a study. Abstract: Background: An oral vaccine is a potential tool to tackle the reservoir of Mycobacterium bovis in European badgers ( Meles meles ), which contributes to tuberculosis of cattle in the British Isles. Inferences about vaccine protection against experimental challenge with M. bovis depend on the measurement of tuberculosis. Assessment of tuberculosis in larger species, such as badgers, is typically based on the tuberculous lesions visible at post-mortem examination and histopathology. We have developed a robust scoring system for tuberculous lesions by combining several parallel measures, which we call the "disease burden score" (DBS). Methods: Alternative scoring systems were compared within a regression analysis applied to observations from a total of 168 badgers from eight studies, including 107 badgers subjected to vaccination treatment and 61 non-vaccinated controls. The analysis included incidental observations that were recorded from each badger as potential covariate factors explaining some of the variation among animals sourced from the wild. Results: DBS was found to be the most accurate and reliable of the scoring systems compared. By taking account of significant covariates affecting disease, application of the DBS reduced residual variance by 22.9%. A previously used measure, based on assessment of visible lesions, was suboptimal due to non-uniform variance that increased with expected value, although square root transformation addressed this issue. The covariate model fitted to DBS included sex (males had higher DBS), weight (negatively associated with DBS) and immunological evidence of prior exposure to Mycobacterium avium (positively associated with DBS). Conclusions: We identified improved measures of tuberculous disease derived from data already collected. We also demonstrated that the proper scaling of measurements of disease in such models is necessary and can be determined empirically. The covariates which were most strongly associated with the severity of disease are important in experimental studies involving outbred animals with variable background.